Direction on Digital Technology Adoption for SMEs Before, During and After the Pandemic Covid-19: An Insight from Indonesian SMEs - Hartono, Arif; Roostika, Ratna; Darmawan, Baziedy Aditya (Journal of Ecohumanism, 2024)
This study explores the digital transformation strategies adopted by small and medium enterprises (SMEs) in Indonesia’s creative industries before, during, and after the COVID-19 pandemic. Through a qualitative approach involving semi-structured interviews with five SME owners and managers in Yogyakarta, this research examines how SMEs adapted their business models and operations to ensure resilience amid unprecedented disruptions. Findings indicate that, initially, SMEs showed limited digital engagement due to perceived value challenges and digital literacy gaps. However, during the pandemic, the necessity to survive led to rapid digital adoption, including e-commerce platforms, digital payments, and customer relationship management tools. Collaborative partnerships with logistics and marketing providers became essential for business continuity, demonstrating the value of ecosystem-based strategies. In the post-pandemic phase, SMEs increasingly viewed digital transformation as a core strategy, investing in digital skills, infrastructure, and long-term digital strategies for scalability and growth. This study contributes to the literature by offering a phased perspective on digital transformation, highlighting how a crisis-driven response can evolve into a sustainable growth strategy. Policy implications suggest that digital literacy programs, financial incentives, and public-private partnerships could further support SME digitalization in developing economies. This research emphasizes that digital transformation serves as a crisis-response mechanism and a strategic asset, equipping SMEs with resilience and adaptability for future challenges.